1974
DOI: 10.1037/h0035851
|View full text |Cite
|
Sign up to set email alerts
|

Modification of hypnotizability: A review.

Abstract: Beginning with a discussion of the domain of hypnotic behavior, the controversy between clinical and experimental hypnotists concerning the modification of the ability to be hypnotized is presented. The-next four sections deal with the evidence demonstrating that responsiveness to hypnosis can be meaningfully altered. Modification studies are discussed in relation to sensory alterations, hypnotic set and environmental setting situational variations, training experiences in nonhypnotic behavior, and training in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 143 publications
4
24
0
Order By: Relevance
“…No, those may be achieved in other ways, such as by strong social pressure (Barber, 1969) or simply by the desire of a well-informed subject to deceive an onlooker (Orne, 1971). The altered subjective state that accompanies a hypnotic procedure may be approximated by monotonous environments (Barabasz, 1982), meditation or drugs (Diamond, 1974), or the hypnogogic state that borders sleep (Delmonte, 1984;Schacter, 1976). It is the constellation of the hypnotic situation (efficient cause) and able and willing subjects (necessary causes) resulting in altered responses (HRs)-both objective (e.g., inability to make certain responses, effortlessness of other responses) and subjective (e.g., reports of altered sensations)-that constitute hypnosis.…”
Section: The First Cause Of Hypnosis: Efficient Causesmentioning
confidence: 99%
“…No, those may be achieved in other ways, such as by strong social pressure (Barber, 1969) or simply by the desire of a well-informed subject to deceive an onlooker (Orne, 1971). The altered subjective state that accompanies a hypnotic procedure may be approximated by monotonous environments (Barabasz, 1982), meditation or drugs (Diamond, 1974), or the hypnogogic state that borders sleep (Delmonte, 1984;Schacter, 1976). It is the constellation of the hypnotic situation (efficient cause) and able and willing subjects (necessary causes) resulting in altered responses (HRs)-both objective (e.g., inability to make certain responses, effortlessness of other responses) and subjective (e.g., reports of altered sensations)-that constitute hypnosis.…”
Section: The First Cause Of Hypnosis: Efficient Causesmentioning
confidence: 99%
“…Thus defining the situation as a test of gullibility produced a negative modeling set and thereby reduced hypnotic responsiveness. Other researchers (see Diamond, 1974, for a review) have found altering the definition of the situation had similar effects.…”
Section: Social Learning Theorymentioning
confidence: 82%
“…However, Eysenck (1943) and Weitzenhoffer and Weitzenhoffer (1958) found the sex of the hypnotist-model had no effect on hypnotic suggestibility. Finally, Diamond (1974) concluded in his review of the literature that characteristics of the hypnotist-model which evoke the confidence and trust of the hypnotic subject facilitates hypnotic suggestibility.…”
Section: Social Learning Theorymentioning
confidence: 98%
“…Laboratory investigators, through the development of standardized hypnotizability rating scales, have con firmed the clinical observation and enlarged upon it [Hilgard, 1965], We know from a survey of many thousands of subjects that hypnosis is not experienced in similar fashion by all. Hypnotizability is not universally dis tributed, and the capacity to experience it seems to be remarkably stable [Diamond, 1974]. This means that poor subjects are not likely to become good ones, and that good subjects, provided the circumstances are appro priate, will generally respond well.…”
Section: Hypnosismentioning
confidence: 99%